Comparing induction of labour with oral misoprostol or Foley catheter at term: cost‐effectiveness analysis of a randomised controlled multi‐centre non‐inferiority trial. (8th August 2017) - ten Eikelder, MLG; van Baaren, G‐J; Oude Rengerink, K; Jozwiak, M; de Leeuw, JW; Kleiverda, G; Evers, I; de Boer, K; Brons, J; Bloemenkamp, KWM; Mol, BW
Abstract : Objective: To assess the costs of labour induction with oral misoprostol versus Foley catheter. Design: Economic evaluation alongside a randomised controlled trial. Setting: Obstetric departments of six tertiary and 23 secondary care hospitals in the Netherlands. Population: Women with a viable term singleton pregnancy in cephalic presentation, intact membranes, an unfavourable cervix (Bishop score <6) without a previous caesarean section, were randomised for labour induction with oral misoprostol ( n = 924) or Foley catheter ( n = 921). Methods: We performed economic analysis from a hospital perspective. We estimated direct medical costs associated with healthcare utilisation from randomisation until discharge. The robustness of our findings was evaluated in sensitivity analyses. Main outcome measures: Mean costs and differences were calculated per women induced with oral misoprostol or Foley catheter. Results: Mean costs per woman in the oral misoprostol group and Foley catheter group were €4470 versus €4158, respectively [mean difference €312, 95% confidence interval (CI) –€508 to €1063]. Multiple sensitivity analyses did not change these conclusions. However, if cervical ripening for low‐risk pregnancies in the Foley catheter group was carried out in an outpatient setting, with admittance to labour ward only at start of active labour, the difference would be €4470 versus €3489, respectively (mean difference €981, 95% CI €225–1817). Conclusions: Oral misoprostol and Foley catheter generate comparable costs. Cervical ripening outside labour ward with a Foley catheter could potentially save almost €1000 per woman. Tweetable abstract: Oral misoprostol or Foley catheter for induction of labour generates comparable costs. Tweetable abstract: Oral misoprostol or Foley catheter for induction of labour generates comparable costs.